Art captured in square - Mansor, Musliyana; John, Leong (Universiti Putra Malaysia Press, 2015)
Smartphone technology has changed how people are using the phone to communicate and now, in photography too. Anyone who has a smartphone, can snap a photo in an instant and share it to the world through all social media networks. With the advancement in technology, people can snap photo effortlessly. Combined with multiple editing apps, this results in a whole new perspective and appreciation of mobile photography. Being the founder of the most popular photo sharing app, Instagram, Kevin Systrom once said, “Our mission is to capture all the world’s moments, but our core value is to inspire creativity”. What a successful mission! Every user of Instagram is basically an artist now. They have to think like an artist in every photo; creating something new and unique, while considering the angle, colour, creativity and storylines of their artistic images. Some people have even surpassed the initial purpose by generating money out of photo sharing apps, demonstrating true zeitgeist of Generations Y and Z, where freedom of shoot and share are encouraged worldwide.